Chapter 5 – Using simple data: surplus production models - Santos, Jorge (Septentrio Educational, 2015)
QUESTIONS ASKED • How to assess the state of a fishery with a simple series of catch and effort? • How is a fishery model different from a trend analysis? • Do the assumptions of the model affect the management values of interest? • How to word a management advice? Surplus production equilibrium and dynamic models